A Transformational Leadership Model for School Principals in Accelerating the Digital Transformation of Vocational High School Management Toward SDG 4 - Yohanes Eko Prasetyo Prasetyo; Yatim Riyanto; Nunuk Hariyati (Journal of Current Studies in SDGs, 2027)
Objective: To analyze the role of transformational leadership in accelerating the digital transformation of technology-based school management in vocational high schools and to explore leadership strategies employed by school principals in supporting sustainable digital innovation. Method: A qualitative approach with a multi-case study design was employed at Mitra Sehat Mandiri Vocational High School Sidoarjo and Vocational High School  1 Sidoarjo. Data were collected through in-depth interviews, observations, and document analysis involving principals, vice principals, teachers, administrative staff, and school operators. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while credibility was ensured through triangulation, member checking, and prolonged engagement. Result: The findings indicate that both schools have successfully integrated digital technologies into learning, administration, communication, and decision-making processes. Transformational leadership emerged as a key factor in establishing a digital vision, identifying the potential of educators and educational staff, facilitating professional development, and supporting organizational adaptation to technological change. Continuous principal support through infrastructure provision, training, mentoring, and evaluation significantly improved digital readiness and institutional effectiveness. Furthermore, the study identified two complementary pathways of digital transformation, namely system-driven and culture-driven approaches, which collectively contribute to sustainable organizational change. Novelty: To develop of a conceptual model of technology-based school management transformation that integrates transformational leadership, organizational culture, human resource readiness, and technological infrastructure as toward SDGs 4. The findings suggest that sustainable digital innovation in vocational education requires a balanced integration of system-oriented and culture-oriented transformation strategies.